دراسة العلاقة السببية طويلة الأجل بين التنويع الاقتصادي والنمو الاقتصادي في الجزائر للفترة (1990-2019) - منصوري, عبد الوهاب (جامعة الوادي - University of Eloued, 2023)
This study aimed to try to highlight the importance of economic diversification and its impact on economic growth by finding the long-term causal relationship between the two variables in Algeria for the period (1990-2019) using the Toda and Yamamoto 1995 methodology to test causality, which is based on the VAR autoregressive vector model. The results of this study showed the absence of a causal relationship between the independent variable, the value added of medium and high-tech industries, which expresses economic diversification, and per capita GDP, which expresses economic growth, with a causal relationship between each of the two independent variables, oil resource revenues as a percentage of gross domestic product and value Additives in the agricultural sector (a percentage of GDP) as expressive of economic diversification and economic growth
Studying the long-term causal relationship between economic diversification and economic growth in Algeria for the period (1990-2019)
مقال
Keywords: التنويع الاقتصادي ; النمو الاقتصادي; Economic diversification; Economic growth; Causal relationship. Toda and Yamamoto .1995